Assessment of healthcare facilities’ readiness to provide antenatal care in Ethiopia: facility based study using service provision assessment data - Addisu Alehegn Alemu; Alec Welsh; Theodros Getachew; Marjan Khajehei (Archives of Public Health)
Abstract Background Readiness of healthcare facilities is essential for delivering quality healthcare services. There is limited evidence on the antenatal care (ANC) readiness of healthcare facilities in Ethiopia. This study aimed to assess the readiness of ANC services and its influencing factors in Ethiopian healthcare facilities. Methods A secondary data analysis was performed using data from the Ethiopian Service Provision Assessment conducted from 11th August 2021 to 4th February 2022. A total of 905 healthcare facilities from nine regions and two city administrations in Ethiopia that provided ANC were included. Healthcare facilities’ ANC readiness was evaluated using 22 indicators across five domains: trained staff and ANC guidelines (3), basic medical equipment (4), medicines and commodities (4), infection prevention tools (6), and diagnostic tests (5). A higher score in each domain indicated greater readiness to deliver recommended ANC. A Generalized Poisson regression model identified factors influencing each domain of ANC readiness indicators. Data analysis was conducted using Stata software version 16. Results The total number of ANC readiness indicators in healthcare facilities ranged from two to seventeen. The mean score for each indicator of ANC readiness in healthcare facilities was as follows: trained staff and guidelines (1.36/3, SD = 0.96), basic medical equipment (3.20/4, SD = 0.99), medicines and commodities (1.95/4, SD = 1.36), infection prevention tools (4.33/6, SD = 1.51), and diagnostic tests (2.22/5, SD = 1.80), based on the included indicators in each domain. Regression results showed lower availability of medicines and commodities, infection prevention tools, and diagnostic tests in clinics and rural facilities. Trained staff and ANC guidelines were less available in private healthcare institutions, health posts, and clinics. Conversely, medicines and commodities were more available in healthcare facilities in the Afar, Amhara, and Somali regions. Conclusion Most healthcare facilities in Ethiopia lacked key ANC readiness indicators, which are crucial for comprehensive ANC and achieving maternal and child health Sustainable Development Goals. Strategic interventions are needed to ensure ANC readiness indicators are available in healthcare facilities and to address disparities by facility type, managing authority, location and region.